2013
DOI: 10.9745/ghsp-d-13-00002
|View full text |Cite
|
Sign up to set email alerts
|

Operations research to add postpartum family planning to maternal and neonatal health to improve birth spacing in Sylhet District, Bangladesh

Abstract: This quasi-experimental study integrated family planning, including the Lactational Amenorrhea Method, into community-based maternal and newborn health care and encouraged transition to other modern methods after 6 months to increase birth-to-pregnancy intervals. Community-based distribution of pills, condoms, and injectables, and referral for clinical methods, was added to meet women's demand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 27 publications
0
37
0
Order By: Relevance
“…Nevertheless, when postpartum women are exposed to postpartum family planning messages during other visits to health facilities, such as during labor and delivery, they are more likely to adopt a modern method [30,31]. In addition, community-based programs can increase the use of effective contraceptive methods in the postpartum period [32].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, when postpartum women are exposed to postpartum family planning messages during other visits to health facilities, such as during labor and delivery, they are more likely to adopt a modern method [30,31]. In addition, community-based programs can increase the use of effective contraceptive methods in the postpartum period [32].…”
Section: Discussionmentioning
confidence: 99%
“…However, we emphasize that nearly all studies had short observation periods. With the exception of the Bangladesh study reported by Baqui (2011) and Ahmed et al (2013), no study covered here examined the continuation of contraceptive use following the intervention or the impact on pregnancy risk beyond the first postpartum year. Thus, we know little about continuation of contraceptive use after specific interventions and about the impact of interventions on birth spacing.…”
Section: Discussionmentioning
confidence: 99%
“…We identified ten projects, including three RCTs, that delivered interventions both before and after delivery ( Table 3). Five of these, in Bangladesh, Egypt, India (two), and South Africa, involved numerous activities, including home visits, domiciliary provision of contraceptive supplies, explicit incorporation of husbands, and community involvement (Kunene et al 2004;Varkey et al 2004;Abdel-Tawab, Loza, and Zaki 2008;Baqui et al 2011;Sebastian et al 2012;Ahmed et al 2013). The Bangladesh and Egyptian studies complemented facility-based counseling with home visits and community activities.…”
Section: Combined Ante-and Postnatal Interventionsmentioning
confidence: 99%
“…This study is a sub-study of the Healthy Fertility Study (HFS), 2 which was conducted in Sylhet District in northeastern Bangladesh [8]. In Sylhet District, in 2011, almost half (46.5%) of non-first births occurred at short intervals of less than 36 months since the previous birth [9].…”
Section: Introductionmentioning
confidence: 99%